Screening for symptoms of anxiety and depression in patients admitted to a university hospital with acute coronary syndrome - Meneghetti,Carolina Casanova (2017)
Abstract Objective: To investigate the prevalence of anxiety and depression in patients admitted for acute coronary syndrome to a university hospital and to examine associations with use of psychotropic drugs. Methods: Ninety-one patients who had had an acute coronary event were enrolled on this cross-sectional prevalence study. Characteristics of the study population and the prevalence rates of depression and anxiety in the sample were assessed using the Hospital São Lucas da Pontifícia Universidade Católica do Rio Grande do Sul (PUCRS) psychiatric consultation protocol, which includes clinical and sociodemographic data, and the Hospital Anxiety and Depression Scale (HADS). Results: The prevalence of symptoms of anxiety was 48.4% (44 patients) and the prevalence of depressive symptoms was 26.4% (24 patients). Of these, 19 patients (20.9% of the whole sample) had scores indicative of both types of symptoms concomitantly. Considering the whole sample, just 17 patients (18.7%) were receiving treatment for anxiety or depression with benzodiazepines and/or antidepressants. Conclusions: Anxiety and depression are disorders that are more prevalent among patients with acute coronary syndrome than in the general population, but they are generally under-diagnosed and under-treated. Patients with anxiety and depression simultaneously had higher scores on the HADS for anxiety and depression and therefore require more intensive care.